Using Think-Ahead and Write Strategy to Improve Student’s Reading Ability in English Learning - Nurcholisyah Rizki Ditanti Mutmainnah; Muhamad Sofian Hadi; Aswir Aswir (Jurnal Studi Guru dan Pembelajaran, 2021)
This study aims to determine which strategy is the most effective in improving students' reading skills in English Learning. This study used two comparison classes, namely the experimental class and the control class at MTs Khazanah Kebajikan. In the experimental class, class VIII A uses the Think-Ahead and Write strategy. While the control class uses class VIII B with conventional methods. Based on the data obtained by the researcher, the results of the t-test of this study were 3.92007, while for the t-table with levels of 0.05 and 28 degrees of freedom obtained 1.70113. The calculation results show that the t-observation is 3.92007 > tt (t-table) 1.70113. The alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. The results of the class research above show that the implementation of Think-Ahead and Write strategies as an effort to improve students' reading skills is effective and efficient.